Some Characterization Results on Dynamic Cumulative Residual Tsallis Entropy - Madan Mohan Sati; Nitin Gupta (Journal of Probability and Statistics)
We propose a generalized cumulative residual information measure based on Tsallis entropy and its dynamic version. We study the characterizations of the proposed information measure and define new classes of life distributions based on this measure. Some applications are provided in relation to weighted and equilibrium probability models. Finally the empirical cumulative Tsallis entropy is proposed to estimate the new information measure.